2006
DOI: 10.1117/12.678994
|View full text |Cite
|
Sign up to set email alerts
|

Coherent phenomena in a semiconductor quantum well system: effects of double dark states

Abstract: We analyze the steady state and transient properties of the polarization and of the electronic population in a triple semiconductor quantum well structure with tunneling induced interference. We first derive the dark states of the system and show that this structure can lead to double dark states. Then, we show that under the dark state conditions the system can exhibit tunneling induced transparency, slow light, transient gain without inversion and coherent population trapping. The dynamics of the polarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Our study is a natural extension and our model is for a synthesized 4-level electronic system where some theoretical results have been analysed by some researchers. [20,27,28] Based on the technique of quantum coherence in semiconductor quantum well, our theoretical work maybe has a feasibility in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is a natural extension and our model is for a synthesized 4-level electronic system where some theoretical results have been analysed by some researchers. [20,27,28] Based on the technique of quantum coherence in semiconductor quantum well, our theoretical work maybe has a feasibility in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that under the interaction of an electromagnetic field, the constructive interference of the emission spectrum, the tunneling induced interference and the optical bistability could be produced in a triple semiconductor quantum well. [20,27,28] To the best of our knowledge, no further theoretical and experimental work has been carried out to investigate the transmission of slow light in such a triple quantum well interacting with a weak probe field, a strong control field and a pump field, which motivates us to study these phenomena of quantum coherence.…”
Section: Introductionmentioning
confidence: 99%